Decontamination of Minimally-Processed Fresh Lettuce Using Reuterin Produced by Lactobacillus reuteri - Asare, Paul T.; Greppi, Anna; Stettler, Martina; Schwab, Clarissa; Stevens, Marc J. A.; Lacroix, Christophe (Frontiers in Microbiology, 2018)
Over the last years the demand for pre-washed, fresh-cut, minimally-processed (MP) produce has increased. MP fresh vegetable are rapidly spoiled, whereas there is consumers’ concern about chemical disinfection treatments such as with chlorine. A promising antimicrobial is reuterin, a broad-spectrum-antimicrobial compound produced by food-grade Lactobacillus reuteri from glycerol. In aqueous solution, reuterin is a dynamic system consisting of 3-hydroxypropionaldehyde (3-HPA), its hydrate, its dimer as well as acrolein, which was recently identified as the main antimicrobial component of the system. Here, we tested the use of reuterin containing similar 3-HPA levels but different acrolein concentrations for decontaminating and preserving fresh-cut lettuce. Crude reuterin (CR) was produced by biotransformation of 600 mM glycerol using L. reuteri DSM 20016T. CR preparations were further incubated for 16 h at 50 °C to produce enhanced reuterin (ER) with raised concentration of acrolein. Fresh-cut iceberg lettuce (Lactuca sativa) was washed using CR (1.5 to 1.9 mM acrolein) and ER (7.2 to 21.9 mM acrolein) solutions at 4 oC, or sodium hypochloride (250 mg/L) and tap water, and compared with unwashed lettuce. Washed lettuce samples were packed under modified atmosphere (2% O2, 5% CO2 and 93% N2) and stored for 13 days at 4 oC. Application of ER containing 12.1, 20.9 or 21.9 mM acrolein reduced the initial viable plate counts of Enterobacteriaceae (by 2.1 - 2.8 log CFU/g), and yeasts and moulds (by 1.3 - 2.0 log CFU/g) when compared with unwashed samples. In contrast, reuterin solutions containing 7.2 mM acrolein, sodium hypochlorite and tap water only showed very limited and transient, or no effects on the cell loads of lettuce after washing and during storage. Visual assessment of leaves washed with ER showed discoloration after 7 days of storage while other treatments preserved the aspect of washed lettuce. Our data show the predominant role of acrolein as the main antimicrobial component of the reuterin system for food biopreservation. Reuterin preparations with enhanced acrolein concentration of 12.1 mM and higher were effective to significantly reduce the microbial load of washed lettuce during 13 days, potentially enhancing product safety.